2018
DOI: 10.5539/elt.v11n10p1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Chadian Learners/ Speakers of English’s Pronunciation

Abstract: With the development of English as the world’s lingua franca, there is a serious rush for the language by many countries, which have no past history with Britain, the US or any other country of the Inner Circle (Kachru 1988). Chad, which was colonized by France is one of those countries (Anderson 2008). In those countries, where English is generally learnt as a foreign language by an elitist group, the language progressively develops and has local stable features among it speakers. With the increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These factors predict various difficulties, notably, segmental and supra-segmental errors that will be committed by learners (Nkongho, 2021). To illustrate, results of another recent study (Safotso, 2018) analysing the speech produced by some post-graduate Chadian students, confirmed that Chadian learners of English actually face difficulties in articulating most English consonants and vowels as well as the placement of correct word stress. These deviances in phoneme articulation and word stress placement, undoubtedly, resulted from the negligence of pronunciation instruction through the above mentioned educational factors.…”
Section: Discussion Of Findingsmentioning
confidence: 87%
“…These factors predict various difficulties, notably, segmental and supra-segmental errors that will be committed by learners (Nkongho, 2021). To illustrate, results of another recent study (Safotso, 2018) analysing the speech produced by some post-graduate Chadian students, confirmed that Chadian learners of English actually face difficulties in articulating most English consonants and vowels as well as the placement of correct word stress. These deviances in phoneme articulation and word stress placement, undoubtedly, resulted from the negligence of pronunciation instruction through the above mentioned educational factors.…”
Section: Discussion Of Findingsmentioning
confidence: 87%
“…For the past twenty years, Chadian learners and users of English have been having a strong interest in the language. Their number in Cameroonian, Nigerian, Ghanaian and Sudanese universities as well as in linguistic centres in N'Djamena testifies to this (Anderson, 2008;Safotso, 2018;Safotso & Ndoubangar, 2018). It can be pointed out that the petrol boom in the country has really changed the attitudes of Chadians towards the English language.…”
Section: Introductionmentioning
confidence: 84%
“…However, there is a problem concerning the efficient use of the standard varieties as many factors cause important deviations. To date very little research has been carried out on English in Chad (Anderson, 2008;Safotso, 2018;Safotso & Ndoubangar, 2018, 2020. Most information can rather be found in students' dissertations (Alladoum, 2014;Ndoubangar, 2018;Titibeye, 2020;Ngaidandi, 2021;Tao, 2021), etc.…”
Section: Introductionmentioning
confidence: 99%